#TITLE_ALTERNATIVE# - PURNAWAN (NIM 23704010), BENNY
Undetected foreign object damage (FOD) will eventually cause catastrophic failure. Since obtaining real dent surface caused by FOD was very difficult, the damage surface were artificially created in this research. The FOD were simulated by hitting a specimen with air soft gun bullet at a speed of 120 m/s; approximately of 3.83 J at kinetic energy. FOD simulation on aluminum, steel and titanium plates resulted in the distinctive damage behavior among those three specimens. Severe damage was observed in the aluminum specimen in contrast to the titanium surface which completely free from damage. The damage level detected in steel surface lies in between the damage level of aluminum and titanium. In this research, the damage level of three types of materials will be correlated with the modulus of resilience.